2004
DOI: 10.1016/j.cub.2003.11.022
|View full text |Cite
|
Sign up to set email alerts
|

Zebrafish pou5f1/pou2, Homolog of Mammalian Oct4, Functions in the Endoderm Specification Cascade

Abstract: pou5f1, also known as Oct4, is required to establish the pluripotent cell population necessary for embryogenesis in mouse. Additional roles during development, including endoderm formation, have been proposed. In zebrafish, the zygotic pou5f1/pou2 mutant spiel ohne grenzen (spg) shows neural plate patterning defects and reduced endoderm at the tailbud stage. To investigate the function of maternal and early zygotic pou5f1 expression, we rescued zygotic spg(m793) mutants by injecting pou5f1 mRNA at the one-cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
163
1

Year Published

2005
2005
2011
2011

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 136 publications
(169 citation statements)
references
References 37 publications
5
163
1
Order By: Relevance
“…Mosaic gene expression is a hallmark of embryonic development in notably mouse (Rossant and Tam, 2009) and zebrafish (Sprague et al, 2003;Lunde et al, 2004;Sprague et al, 2006) and may be at the origin of lineage specification. Whole-mount in situ hybridization of MBT + embryos showed that sox3 was ubiquitously expressed (Fig.…”
Section: Mosaic Klf4 Expression In Embryos Correlates With Co-detectimentioning
confidence: 99%
“…Mosaic gene expression is a hallmark of embryonic development in notably mouse (Rossant and Tam, 2009) and zebrafish (Sprague et al, 2003;Lunde et al, 2004;Sprague et al, 2006) and may be at the origin of lineage specification. Whole-mount in situ hybridization of MBT + embryos showed that sox3 was ubiquitously expressed (Fig.…”
Section: Mosaic Klf4 Expression In Embryos Correlates With Co-detectimentioning
confidence: 99%
“…pou2 plays a zygotic role in the establishment of the midbrain-hindbrain organizer (Schier et al, 1996;Belting et al, 2001;Burgess et al, 2002;Reim and Brand, 2002). An earlier pou2 function for endoderm initiation was detected through analysis of maternal-zygotic (MZ) spg mutant embryos (Reim et al, 2004;Lunde et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Further, maternally contributed wild-type Crsp34 protein may partially rescue zygotic requirements for Crsp34 in mutant embryos during early phases of development. This constellation might mimic a specific function of Crsp34 in the formation of cell types that differentiate late in development, due to lower residual levels of maternal protein (compare to maternal rescue of zygotic functions for the Nodal coreceptor oep and pou5f1/spg genes described in Gritsman et al 1999 andLunde et al 2004). However, in crsp34 m885 mutant embryos a reduction of cells is observed in the ganglion and amacrine cell layers, whose progenitors lessen mutant siblings reveals a lower density in the central region of the mutant retina.…”
Section: Discussionmentioning
confidence: 99%